The Effect of Cosmetics Packaging Design on Consumers' Purchase Decisions - Mohamed, Nada Bahgat Abdelazim; Medina, Irene GarcÃa; Romo, Zahaira González (Indian Journal of Marketing, 2018)
This research provided new helpful insights for cosmetics marketers about their consumer preferences regarding visual elements of their hairstyle, skin care, and makeup products. A quantitative research approach was adopted using the survey research design and used a questionnaire tool to achieve the research objectives. Data were collected and analyzed from 130 female cosmetics respondents. Previous research studies from academic journals, articles, and books were also used as secondary resources. The findings showed that cosmetics consumer behaviour was, in fact, affected by the visual elements of the cosmetics package designs and thus affected the consumers' purchase intentions. Moreover, material and colours of the hairstyle, skin care, and makeup products packages were proved to be of high importance with respect to the level of attractiveness and affected consumers' preferences.